Synergistic effect of Celastrus paniculatus and Tribulus terrestris against chronic immobilisation stress-induced memory impairment, BDNF level and neuroinflammation - Babiker Bashir Haroun Baraka, Bhagya Venkanna Rao, Tanuja Krishnamurthy (Journal of Applied Pharmaceutical Science, 2025)
Long-term stress exposure induces anxiety, depression, and cognitive impairment. Previous research has established a correlation between chronic stress, memory deficits, and behavioral changes linked to neuroinflammation. Studies in both preclinical and clinical settings have highlighted the remarkable protective characteristics of herbal medicines. This research seeks to explore the positive impacts of Celastrus paniculatus Willd. (CP) and Tribulus terrestris L. (TT) in an experimental model of depression. Wistar rats were exposed to stress for 2 hours per day for 10 days in immobilization bags. After the stress induction, these rats were orally administered CP oil (400 mg/kg/day) and an ethanolic extract of TT (250 mg/kg/day) for 2 weeks. The observed increase in anxiety-like behavior, depressive-like behavior, and memory impairment in stressed rats aligns with previous research linking chronic stress exposure with neuropsychiatric disorders and cognitive dysfunction. The elevation of interleukin 6 (IL-6) and tumor necrosis factor-alpha, along with decreased brain-derived neurotrophic factor (BDNF) levels, further supports the involvement of neuroinflammation and neurotropic factors in stress-induced pathophysiology. The significant improvement in anxiety, depression, and memory deficits following CP and TT treatment suggests their potential as therapeutic agents against stress-related disorders. The restoration of BDNF levels and attenuation of neuroinflammation in the prefrontal cortex and hippocampus underscore the mechanisms through which CP and TT exert their beneficial effects. Overall, our research highlights the importance of exploring natural compounds like CP and TT as potential adjunctive therapies for stress-related neuropsychiatric disorders, offering safer and potentially more accessible alternatives to conventional pharmacotherapy.
Keywords: Tribulus terrestris, Celastrus paniculatus, chronic immobilization stress, BDNF, cytokines, hippocampus, and frontal cortex